(untitled) (Revista Latino-Americana de Enfermagem, 2002)
A worldwide shortage of nurses has been acknowledged by the multidisciplinary Global Advisory Group of the World Health Organization. The shortage is caused by an increased demand for nurses, while fewer people are choosing nursing as a profession and the current nurses worldwide are aging. The shortage applies to nurses in practice as well as the nurse faculty who teach students. The inter-country recruitment and migration of nurses from developing countries to developed countries exacerbates the problem. Although public opinion polls identifies the nurse as the person who makes the health care system work for them, the conditions of the work environment in which the nurse functions is unsatisfactory and must change. Numerous studies have shown the positive effects on the nurse of a healthy work environment and the positive relationships between nursing care and patient outcomes. It is important that government officials, insurance companies, and administrators and leaders of health care systems acknowledge and operationalize the value of nurses to the health care system in order to establish and maintain the integrity and viability of that system.